Safety considerations for performing robotic surgery in the presence of a permanent pacemaker. Issue 7 (July 2019) - Ubee, Sarvpreet S; Selvan, Masilamani; Chandrashekar, Rangaswamy; Cooke, Peter
With increasing experience, more complex patients are undergoing robotic surgery but the patient safety during these procedures remains paramount. Being a relatively recent technique of minimal access surgery, the safety and feasibility of robotic surgery is still under scrutiny. We recently performed two robotic procedures in patients who have permanent cardiac pacemaker. We believe this is the first published report through which it is shared and discussed, the preoperative and intraoperative management for these patients along with the importance of WHO checklist for safely performing robotic procedures. The importance of pre-procedure planning and briefing cannot be emphasised enough as these along with intraoperative management remain the key step in dealing with an adverse cardiac event due to permanent pacemaker malfunction.